Out-of-pocket costs near end of life in low- and middle-income countries: A systematic review - Eleanor Reid; Arunangshu Ghoshal; Aisha Khalil; Jingjing Jiang; Charles Normand; Alexandria Brackett; Peter May (Public Library of Science (PLoS), 2022)
Background Globally, there is a rise in chronic disease, including cancer, major organ failure and dementias. Patients and their families in low- and middle-income countries (LMICs) pay a high proportion of medical costs out of pocket (OOP), and a diagnosis of serious illness often has catastrophic financial consequences. We therefore conducted a review of the literature to establish what is known about OOP costs near end of life in LMICs. Aims To identify, organise and report the evidence on out-of-pocket costs in adult end-of-life populations in LMIC. Methods A systematic search of 8 databases and a hand search of relevant systematic reviews and grey literature was performed. Two independent reviewers screened titles and abstracts, assessed papers for eligibility and extracted data. The review was registered with PROSPERO and adhered to the Preferred Reporting items for Systematic Reviews and Meta Analyses. The Mixed Methods Appraisal Tool was used to assess quality. The Wagstaff taxonomy was used to describe OOP. Results After deduplication, 9,343 studies were screened, of which 51 were read and rejected as full texts, and 12 were included in the final review. OOP costs increased with advanced illness and disease severity. The main drivers of OOP were medications and hospitalizations, with high but variable percentages of the affected populations reporting financial catastrophe, lost income, foregone education and other pressures. Conclusion Despite a small number of included studies and heterogeneity in methodology and reporting, it is clear that OOP costs for care near end of life in LMIC represent an important source of catastrophic health expenditures and impoverishment. This suggests a role for widespread, targeted efforts to avoid poverty traps. Financial protection policies for those suffering from incurable disease and future research on the macro- and micro- economics of palliative care delivery in LMIC are greatly needed.